ANALISIS IMPLEMENTASI PROGRAM PENGEMBANGAN KEPROFESIAN BERKELANJUTAN (PKB) BAGI GURU SEKOLAH DASAR - Junaidin Basri; Udin Syaefudin Saud; Asep Suryana; Eka Prihatin (Universitas Pendidikan Indonesia, 2023)
This study aims to describe the implementation of the Continuous Professional Development (PKB) program by elementary school teachers in three Teacher Working Groups (KKG) related to the study of input, process, out put and out come using descriptive qualitative methods. The data were obtained through observation, interview and document review. The results of the study found that SD did not have a PKB work program. The indicators can be seen from the inadequate function of school management in planning, implementing, evaluating, organizing and planning the follow-up after PKB implementation. The results show that the aspects of planning, PKB implementation are carried out by KKG, evaluation system based on PKB SIM, while the follow-up plans for schools and teachers have not been carried out continuously and independently in scientific forum activities based on the needs of teachers and schools. The result is that the implementation of PKB has not had an impact on increasing self-development, the ability of teachers to make scientific work and innovation work. Another obstacle is the lack of budget support from the local government and the weak motivation of teachers to improve their competence. Therefore, a more Participatory, Integrated and Holistic PKB (PKB-PTH) implementation model is needed.